Explaining the perception of spiritual care from the perspective of health personnel: A qualitative study - Zohre Khalajinia; Hoda Ahmari Tehran; Akram Heidari (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Spiritual care is one of the important and essential aspects of healthcare. The impact of spirituality on healing, health-related states, and the ability to cope and adapt to the disease is undeniable. Thus, this study is aimed to explain the perception of the spiritual care of patients by health-care providers. MATERIALS AND METHODS: The present study was performed with a qualitative approach using content analysis by the conventional method in hospitals of Qom University of Medical Sciences. The data were collected through in-depth semi-structured interviews with 11 participants through a purposeful sampling method and analyzed simultaneously. The consistency of the data was confirmed by the participants. RESULTS: Data analysis provided four main categories as follows: "Observing the patient's rights" with subcategories of respect, right to choose, preserving the patient's privacy, proper communication with the patient, "professionalism" with subcategories of responsibility, acceptance of mistakes, development of technical skills and knowledge, "supportive behaviors" with subcategories of paying attention to emotional and psychological needs and "Strengthening the patient's religious dimension" with subcategories of honoring religious beliefs and providing healthcare along with trust in God. CONCLUSIONS: According to the study findings, spiritual care from the perspective of health-care providers was explained as attention to emotional and psychological needs, reverence for patients' religious beliefs, respect for human dignity, and sense of responsibility.